Milk Other Than Breast Milk and the Development of Asthma in Children 3 Years of Age. A Birth Cohort Study (2006–2011) - Asmaa El-Heneidy (8844911) (2018)
Prevalence of asthma in Australian children is amongst the highest in the world. Although breastfeeding positively influences infant immunity, early introduction of Milk Other than Breast Milk (MOTBM) may also play an important role in the development of Asthma. The aim of this study was to investigate the association between the introduction of MOTBM in the first six months after birth and the development of reported persistent asthma in 3-year olds. A sample of 1121 children was extracted from the Environments for Healthy Living longitudinal birth cohort study. Introduction of MOTBM during the first six months after birth increased almost two-fold the risk of development of persistent asthma after adjusting for other covariates (Adjusted Relative Risk (ARR): 1.71, 95% CI: 1.03–2.83, p = 0.038). This study indicates that the introduction of MOTBM in the first six months of life is a risk factor for asthma incidence among 3-year old children. This result is important in explaining the benefits of breastfeeding as part of public health interventions to encourage mothers to increase breastfeeding initiation and duration, and avoid the introduction of MOTBM in the first six months after childbirth. Other Information Published in: Nutrients License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/nu10111798